Self-Efficacy and Social Withdrawal Among Secondary School Adolescents in Kwara State - Hassan Ahmed, Taiye; Abdulkareem, Habibat Bolanle; Kamil Lasisi, Adekola (Universitas Mercu Buana Yogyakarta, 2023)
Secondary school teenagers' social retreat was examined in relation to self-efficacy and gender. The study is guided by two goals, two research questions, and two research hypotheses. It was conducted using a descriptive research correlational design. 100 youths were randomly selected from five senior secondary specialised schools. The General Self-Efficacy Scale by The University of Kansas Center (2015) r = 0.86; and the Social Ability Deficiency Scale (SADS/SPS) by Akinade (2017) r = 0.17 were used to collect the data. The Pearson Product Moment Correlation and T-test were used in the study to formulate and test two research hypotheses. Results showed that there is a very strong positive relationship between self-efficacy and social withdrawal (p. 0.05 < r.cal. = 0.863), but there is no significant relationship between male and female adolescents’ social withdrawal behaviour (p. 0.05 < t.cal. = 31.318). Based on the results, the study concluded that self-efficacy has a significant positive relationship with social withdrawal among secondary school adolescents. The study also concluded that female adolescents were more affected by social withdrawal behaviour than their male counterparts. Based on the conclusion, the study recommends, among others that the school management set aside a day for adolescents to engage in co-play. The school counsellors should organise a conference for female adolescents to orientate them more on self-evaluation in order to help them be aware of social withdrawal behaviour symptoms and how to build on their self-efficacy.